Harnessing the Full Potential of Coroners’ Recommendations - Mok, Elena (Victoria University of Wellington Law Review, 2014)
The ability of coroners to make recommendations to various agencies and organisations is inextricably linked with the coroner’s emerging role in death and injury prevention. Despite this, there is no legal obligation in New Zealand for agencies and organisations to respond to, or implement, proposed changes, which has led to claims that recommendations are being overlooked. However, concerns have also been raised about the quality of some recommendations, especially whether coroners have sufficient expertise to be proposing wide-ranging legal and policy reforms. This article analyses the extent to which recommendations are being implemented by the agencies and organisations to whom they are directed, and addresses whether the criticisms levelled at recommendations are valid. It is contended that greater transparency and accountability is needed in coronial processes to fully harness the preventive and therapeutic potential of coroners’ recommendations.